The Effect Of Using Memrise Application To Improve Students’ Memorization Of Irregular Verb - Monica, Theresia (Unit Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Agama Islam Hubbulwathan, Duri, Indonesia, 2023)
This research was carried out to find out The Effect of Using Memrise Application to Improve Students’ Memorization of Irregular Verb. This research used quantitative approach. The population of this research was the tenth grade of SMAN 3 Mandau. The sample used in this research was divided into the experimental with 36 students and control class with 36 students and the total of the sample was 72 students. The researcher gave 20 questions about irregular verb to collect the data in pre-test and post-test. The finding of t count was -5.372 while the level of significance of 5% was 2.028 in experiment class, and the finding of t count was -7.025 while the level of significance of 5% was 2.028 in control class. Therefore, Ha was accepted and Ho was rejected. In other word, there was significance effect of using Memrise application to improve students’ memorization of irregular verb at the tenth grade SMAN 3 Mandau.